Kelmė and Vaiguva Jewish Communities and Their Perishing in 1941 - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2011)
It is believed that Jews settled in Kelmė in the 15th century and in Vaiguva in the 18th century. In 1897, 2,710 of the 3,914 residents of Kelmė were Jews. In the 20th century, the Kelmė Jewish community shrank, but the town continued to remain an important centre of Jewish (Litvak) culture. In 1937, 1,302 of the 3,599 residents of the town were Jews. The town had a rabbinical school and five synagogues and houses of worship. Prior to the Germany-USSR war, Kelmė (Raseiniai County) may have had approximately 1,350 Jews, while there were over 1,400 Jews in the entire volost, in which a number of Jews were engaged in agriculture. Over the years in the 20th century, the number of Jews living in Vaiguva (Šiauliai County) decreased from 137 (in 1923) to 90–100 (in 1940). Bolshevik-implemented nationalisation and other ‘socialist reforms’ undertaken during the Soviet occupation in 1940–1941 caused great suffering not only for Lithuanians but for Jews as well. Jews were particularly offended by the Bolshevik interference in spiritual matters connected with synagogues and teaching at private schools.
Keywords: Lithuania; German occupation; Jews; Holocaust